A family of model predictive control algorithms with artificial neural networks - Ławryńczuk, Maciej (Zielona Góra: Uniwersytet Zielonogórski)
This paper details nonlinear Model-based Predictive Control (MPC) algorithms for MIMO processes modelled by means of neural networks of a feedforward structure. Two general MPC techniques are considered: the one with Nonlinear Optimisation (MPC-NO) and the one with Nonlinear Prediction and Linearisation (MPC-NPL). In the first case a nonlinear optimisation problem is solved in real time on-line. In order to reduce the computational burden, in the second case a neural model of the process is used on-line to determine local linearisation and a nonlinear free trajectory.
Keywords: predictive control; neural networks; optimisation; linearisation; quadratic programming